The Increasing Mathematical Logic Intelligence Through Problem Based Learning Learning Models in Grade 1 Elementary School Students: Peningkatan Kecerdasan Logis Matematis Melalui Model Pembelajaran Problem Based Learning Pada Siswa Kelas 1 SD - Sari, Yulia Lisa; Anggarini, Vina; Yayuk, Erna (UNIB Press, 2023)
Mathematical logical intelligence is an important ability to have in order to be able to think logically in solving cases or everyday problems related to mathematical calculations. So in cultivating mathematical logical intelligence, it is necessary to stimulate contextual problems through the application of the Problem Based Learning (PBL) learning model. This study aims to explain the application of the Problem Based Learning (PBL) model in instilling mathematical logical intelligence in elementary school students. This research method is classroom action research (CAR), with the implementation of research in two cycles. The stages in this research are: (1) Planning, (2) Acting and Observing, (3) Reflecting. The results showed an increase in mathematical logical intelligence in grade 1 students at Balongjeruk Primary School through the application of the Problem Based Learning (PBL) learning model. The pre-cycle stage shows a logical mathematical intelligence ability of 19%. Cycle 1 showed an increase in the ability of mathematical logical intelligence by 11% to 30%. Cycle 2 shows the ability of mathematical logical intelligence of 12% so that it becomes 52%.